1979
DOI: 10.1037/0003-066x.34.2.107
|View full text |Cite
|
Sign up to set email alerts
|

The rocky road from acts to dispositions.

Abstract: This article examines the attributional error of overestimating dispositions as a cause of behavior, with reference to the attitude attribution paradigm. Earlier experiments were open to criticism on artifactual grounds, but the overattribution-to-persons tendency has proved to be a remarkably robust and easily replicated phenomenon. It can be undermined or overcome when the perceived constraints on behavior are extreme or when instructions specifically set the subject to consider the importance of situational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
468
2
7

Year Published

1987
1987
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 601 publications
(492 citation statements)
references
References 10 publications
15
468
2
7
Order By: Relevance
“…Participants' ratings of how much they and their peers would moderate their initial dispositional inferences about a constrained actors' behavior, made after participants learned that either a dispositional or situational explanatory style conferred significant life advantages. tional influences (Gilbert & Malone, 1995;Jones, 1979Jones, , 1990Ross, 1977). The foregoing studies indicate that people in individualistic cultures expect other social perceivers to be more prone to this correspondence bias than they are themselves.…”
Section: Discussionmentioning
confidence: 89%
“…Participants' ratings of how much they and their peers would moderate their initial dispositional inferences about a constrained actors' behavior, made after participants learned that either a dispositional or situational explanatory style conferred significant life advantages. tional influences (Gilbert & Malone, 1995;Jones, 1979Jones, , 1990Ross, 1977). The foregoing studies indicate that people in individualistic cultures expect other social perceivers to be more prone to this correspondence bias than they are themselves.…”
Section: Discussionmentioning
confidence: 89%
“…Nevertheless, we hesitate to suggest that a selfcausal chunking strategy will completely eradicate the tendency for people to overestimate the role of dispositional factors when interpreting the behavior of others. After all, the tendency to overemphasize dispositional causes of others' behavior is so pervasive that one theorist (Ross, 1977) has dubbed it the "fundamental attribution error" (see also Jones, 1979). Furthermore, some evidence (e.g., Gilbert & Jones, 1986;Gilbert, Pelham, & Krull, 1987;Jones & Harris, 1967) and theorizing (Gilbert, 1987) suggests that it may be impossible to completely wipe out the tendency for people to regard the behaviors of others as reflections of underlying traits.…”
Section: Genera] Discussionmentioning
confidence: 99%
“…Attribution theory says that people in Western cultures typically exaggerate the role of individuals ' motives and intentions while downplaying the role of contextual or societal factors. Psychologist s have termed this the fundamental attribution error (Jones, 1979). Research has shown that certain kinds of news frames tend to encourage this fundamental attribution error of placing responsibility with individuals , while other kinds of news frames are associated with a tendency to attribute responsibilit y more to societal factors than to individuals .…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Despite its greater validity and generalizability, base rate information does not exert a strong effect on the audiences' perceptions or judgments. In fact, people tend to ignore base rate information when even imsy speci®c evidence in the form of exemplars is present (Kahneman & Tversky, 1973).…”
Section: Literature Reviewmentioning
confidence: 99%